Qualitative evaluation of a sports-based mental health literacy program for adolescent males. (September 2021) - Wynters, Rhianna; Liddle, Sarah K.; Swann, Christian; Schweickle, Matthew J.; Vella, Stewart A.
Abstract: Objective: This study aimed to understand adolescent males' experience of participating in a sports-based mental health literacy intervention (Help Out a Mate), and provide insight into their perceptions of the effectiveness and implementation of the program. Method: Thirty-three adolescent males (12–15 years old) who had recently participated in Help Out a Mate took part in six focus groups. Inductive thematic analysis was used to analyse focus group data, and a number of strategies were employed to enhance the trustworthiness of this account, including peer debrief, grounding in examples, and prolonged engagement. Results: These data indicated that these adolescent males broadly had a positive experience of Help Out a Mate and reported that the program was effective in terms of mental health literacy outcomes including increased knowledge of mental health, and increased confidence and intentions to seek and provide help. Delivering the program in the context of sport was reported as engaging, and preferable to delivery in a school context. Whilst some adolescents reported reductions in stigmatising attitudes following the program, others expressed a maintenance of these attitudes, suggesting addressing stigma remains a challenge for mental health literacy workshops. Further, adolescents reported that the program could be improved by including more practical activities and better group management by facilitators. Conclusions: These findings identify important insights into adolescent males' perspectives of the effectiveness and importance of Help Out A Mate as a sports-based mental health literacy intervention, and suggest a number of strategies for improving participation and engagement. Highlights: Adolescents reported a sports-based intervention as a positive experience. Sport was perceived as an appropriate and engaging setting to discuss mental health. Adolescents reported increased confidence to seek and provide helps. Adolescents recommended increasing content engagement and reducing group numbers.